Dormancy, sprouting behavioarr and weight loss in Indian potato (Solanurn tuberosum) varieties - PANDEY, P C; SINGH, S V; PANDEY, S K; SINGH, BWESH (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2004 and 2005 to study the dormancy period, sprout growth and weight loss of 37 Indian potato (Solanurn tuberosurn L.) varieties to estimate the variability in various keeping quality attributes in them. Dormancy period was the longest in 'Kufri Sindhuri' and shortest in 'Kufri Lauvkar'varieties. The number of sproutslper tuber were maximum in 'Kufri Anand' and minimum in 'Kufri Safed' after 60 days of sprouting. Highest length of the longest sprout (5.3 cm) was recorded in 'Kufri Alankar' and 'Kufri Chipsona 1' and lowest (2.1 cm) in 'Kufri Surya' by 60 days. The per cent weight loss after 60 days of sprouting was higher in varieties 'Kufri Jeevan' (12.6%) and 'Kufri Swama' (11.7%) and was lower in varieties 'Kufri Safed' and 'Kufri Chandramukhi' (4.6 and 5.2% respectively). A significant correlation existed between weight loss and number and length of sprouts, whereas with dormancy period, weight loss showed negative correlation.The study indicated that varieties with longer dormancy period, lower number of sprouts per tuber and slower rate of sprout growth are expected to have better keeping quality and hence limited weight loss during storage. Therefore the study suggests potato breeders to consider keeping quality as one of the important characteristic during screening of hybrids.